Extended Survival and Prognostic Factors in Endometrial Cancer: A Multivariate Cox Regression Analysis - Irene Valencia Téllez; Laura De Pablo Zamora; María Castillo Lara; Claudia Vivas Flores; Carlos Vega Reina; Juan Jesús Fernández Alba (Clinical and Experimental Obstetrics & Gynecology)
Background: Endometrial cancer (EC) is the third most prevalent neoplasm among women in Spain and the most frequent malignancy of the female genital tract. The primary risk factors are associated with increased estrogen levels. The objective of our study is to determine the current specific progression-free survival (PFS) and overall survival (OS) in patients with EC at the University Hospital of Puerto Real. Additionally, we aim to understand the independent role of specific factors in the risk of recurrence and mortality from EC through a multivariate analysis. Methods: A retrospective observational survival analysis of a case series was conducted. The study population included all women diagnosed and treated for EC in Spain between January 2010 and December 2021. The Kaplan-Meier method and Cox regression analysis were performed to evaluate survival based on patient age, tumor stage, histological type, and degree of differentiation, and to quantify survival probabilities for each factor. Results: A total of 324 patients were included. The PFS was 86.6% at 5 years and 81.1% at 10 years. The OS was 91.3% at 5 years and 84.8% at 10 years. The tumor-related mortality rate was 9.3% (N = 30) and the tumor recurrence rate was 5.6% (N = 18). The estimated median follow-up using the inverse Kaplan-Meier method was 4.33 years (95% confidence interval (95% CI): 3.72–4.94) for OS and 4.57 years (95% CI: 4.05–5.09) for PFS. The statistically significant factors affecting PFS and OS were age ≥60 years at diagnosis, advanced International Federation of Gynecology and Obstetrics (FIGO) stage (II–IV), non-endometrioid tumor, high tumor grade, and lymphovascular space invasion. Multivariate Cox regression analysis shows that being 60 years or older at the time of diagnosis, advanced FIGO stages, high tumor grade, and serous-papillary tumors are independent risk factors for recurrence or death in EC. Conclusions: Our study shows that being 60 years or older at the time of diagnosis, advanced FIGO stages (II–IV), non-endometrioid EC, higher histological tumor grade, and lymphovascular space invasion are associated with lower OS and PFS. Additionally, multivariate Cox analysis suggests that age ≥60 years at diagnosis, advanced FIGO stages, high tumor grade, and serous-papillary histological type are independent prognostic factors influencing survival and recurrence in EC. This study should serve as a foundation for further research, incorporating relevant aspects of the molecular biology of EC to refine patient prognosis.